2018
DOI: 10.1177/1090198118798679
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Outcomes in Behavior Change Interventions to Prevent Pediatric Obesity: The Role of Dose and Behavior Change Techniques

Abstract: To improve future interventions, greater attention should be paid to the intended and delivered session length, and efforts should be made to facilitate parents' implementation of intervention-recommended activities between sessions (ClinicalTrials.gov, No. NCT01084590).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…The most common retrospective study design was systematic reviews (n=15/23); other retrospective study designs were multi-method study (n=2/23), secondary analysis (n=1/23), methodology study (n=1/23), exploratory study with content analysis (n=1/23), systematic assessment of mobile applications (n=1/23), intervention development (n=1/23), and scoping review (n=1/23). The median number of primary studies assessed in the studies classified as retrospectively applying a BCT taxonomy was 16 and ranged from one [18,19] to 64 [20]. One of the included studies applied a BCT taxonomy both prospectively and retrospectively as it involved adaption of an intervention to a new context [19].…”
Section: Selection Of Sources Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The most common retrospective study design was systematic reviews (n=15/23); other retrospective study designs were multi-method study (n=2/23), secondary analysis (n=1/23), methodology study (n=1/23), exploratory study with content analysis (n=1/23), systematic assessment of mobile applications (n=1/23), intervention development (n=1/23), and scoping review (n=1/23). The median number of primary studies assessed in the studies classified as retrospectively applying a BCT taxonomy was 16 and ranged from one [18,19] to 64 [20]. One of the included studies applied a BCT taxonomy both prospectively and retrospectively as it involved adaption of an intervention to a new context [19].…”
Section: Selection Of Sources Of Evidencementioning
confidence: 99%
“…Of those studies which used the BCTTv1 (n=15), the median number of BCTs reported per study was 5.6, ranging from 4.3 [26] to 9 [27] for published reports. The median number of BCTs reported when including unpublished materials was 17.5, ranging from 13.9 [18] to 45 [28] BCTs. Unpublished materials included items such as manuals for intervention delivery, participant handouts, phone scripts, transcriptions from intervention sessions, and unpublished intervention trial protocols.…”
Section: Selection Of Sources Of Evidencementioning
confidence: 99%
“…Additionally, they are more likely to experience asthma [7], depression, anxiety, and poor psychological well-being [8]. There is a critical need to identify behaviorally-based interventions that will maximize health of youth with severe obesity [9][10][11]. Yet, few studies have identified psychosocial and behavioral factors for severe obesity [12] that could inform such strategies.…”
Section: Introductionmentioning
confidence: 99%
“…8 There is a critical need to identify behaviorally-based interventions that will maximize health of youth with severe obesity. [9][10][11] Yet, few studies have identified psychosocial and behavioral factors for severe obesity 12 that could inform such strategies. This study aimed to examine the psychosocial, behavioral, and clinical correlates of severe obesity in a cohort of youth to identify the contextual and behavioral factors that differentiate those with severe obesity compared to those with non-severe obesity and overweight.…”
Section: Introductionmentioning
confidence: 99%